STUDI TENTANG SUNTING BUNGO SANGGUL DI KENAGARIAN KOTO BARU KECAMATAN KUBUNG KABUPATEN SOLOK - Hasriawati, Leli; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The problem in this research is the most dominant thing happened in Koto Baru Society especially the younger generation is less understanding the meaning contained in edit because there is no special invention book or complete documentation about edit in this Koto Baru Kenagarian. This study aims to describe bungo bun in Kenagarian Koto Baru Kubung District Solok District which includes the design (Motif, Shape / Model) and the meaning contained. This type of research is descriptive qualitative which express, study and interpret the data as it is. Data processed verupa words. Type of data in the form of primary data and secondary data. Data collection techniques using three techniques of observation techniques, interviews and documentation, while the instrument is the research itself. Data analysis in qualitative research is conducted before entering the field, field and after completion of the field, to test the validity of data. The result of this research is obtained motif that used is flower motif of cempaka, jasmine, rose, amethyst, butterfly motif, swallow, elderly bird, and ornament of root vine. Bungo bun shape resembles a triangle on the front, whereas if edit in lentang will have two forms that is on the back of a trapezoidal shape and the front remains triangular. The meaning of the philosophy contained in the bun flowers is a decoration for the head by women while performing the wedding. The back of a trapezoidal-shaped edit symbolizes the chaos.Keywords: Senting bun, Head cover, Koto Baru